Design of Multi-Criteria Spatial Decision Support System (MC-SDSS) for Animal Production - Hesham Ahmed Hassan; Hazem Mokhtar El-Bakry; Hamada Gaber Abd Allah (IAES International Journal of Artificial Intelligence (IJ-AI), 2013)
This paper presents a Multi-criteria spatial decision support system (MC-SDSS) as a tool for decision making and planning. MC-SDSS can be used to assess different criteria with different weights. We believe that such tool can be utilized to help policy/decision makers to improve animal production in Egypt. MC-SDSS facilitates the integration of the exploration and evaluation phases of the decision-making process in a transparent and interactive system that allows policy/decision makers to carry out the analyses without advanced geographical information system (GIS) or multiple criteria decision analysis (MCDA) training. We use weighted overlay method to support data spatial analysis, and then visualize and analyze different factors such as "Diseases", "Climate", "Veterinary care" and "Economical factors" which affect the animal production in Egypt. Policy/Decision makers can change their weights and parameters with this tool for their different study areas. Moreover they can use final suitability maps from this tool.DOI: http://dx.doi.org/10.11591/ij-ai.v2i3.1948